Critical Discourse Analysis on Iwan Fals’ Song Entitled “Minyak Goreng”: A Criticism for The Government - Kusrini, Endang; Muflihah, Muflihah; Sari, Rosdiana Puspita; Pujiyanto, Ambar (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
The scarcity of cooking oil and the increase in its price in Indonesia put society under pressure instead of the fact that Indonesia was the world’s largest palm oil producer. Therefore, Iwan Fals, the singer who often expressed his criticism through a song, also released a sharp criticism song entitled “Minyak Goreng.” Since this song also functioned as a criticism, it contained some linguistic features that were referred to critic the government. This study analyzes Iwan Fals’ song entitled “Minyak Goreng” by using Fairclough’s critical discourse theories. The method used is qualitative with descriptive so that the researcher interprets the data in the lyric based on the happening phenomenon. The data are analyzed in three fields: linguistic features, text production, and social practice. This research shows that Fals uses some linguistic features such as pronouns, similes, metaphors, and probability phrases to express his criticism. Fals also put himself as the people of Indonesia who suffer from this cooking oil scarcity. Besides that, Fals also shows the anger of the people to the government. This research indicates that the text shows the relationship between language, power, and social construction.